The bioactive contents and antioxidant activity of honey bee nest extract of Apis dorsata Binghami from the North Sulawesi - Mokosuli Yermia Semuel; Eva Sherly Nonke Kaunang; Jacklin Stella Manopo (Universitas Jenderal Soedirman, 2019)
Apis dorsata Binghami is a Sulawesi endemic honey bee. Apis dorsata Binghami cannot be bred, so it still lives wildlyin the forests of Sulawesi. However, Apis dorsata Binghami produces more honey, compared to all honey bee species. Furthermore, the diversity of plants as a source of nectar, pollen and plant resin, which is used in the formation of nests and honey is more, than all types of honey bees in the world. Ethnomedically, the Minahasa community has long used honeynest for degenerative diseases such as hyperlipidemia and cancer. Nevertheless, there have been no research reports on bioactive content and bioactivity of Apis dorsataBinghami nest extract. This research wasaimed to determinethe bioactive content of honey bee nest and to obtain the inhibitory concentration 50 (IC50) antioxidant activity of honey bee nest extractofApis dorsata Binghami. Honey bee nest was obtained directly from the forest of Minahasa peninsula, North Sulawesi, Indonesia. Extraction of fresh honey bee nest was conductedusingmaceration method. Bioactive content analysis was carried out by the Harborne method, followed by analysis using UV Vis spectrophotometer and High performance liquid chromatography. IC50antioxidant activity of honey bee nest extract was obtained using DPPH free radical reduction method. The results showed that Apis dorsata Binghami honey bee nest extract containedalkaloids, flavonoids, saponins, tannins, steroids and triterpenoids. Identified flavonoids displayed the highest phytochemical content. Based on the results of HPLC and UV Vis spectrophotometer analysis, there were 20 flavonoid derivatives found in honey bee nest samples in Minahasa. Ethanol extract and n-hexane extract showed high free radical reduction activity compared to vitamin C as a control treatment. However, ethanol extract produced the highest DPPH free radical reduction activity.